On the Fringes of a Christian Kingdom: The White Fathers, Colonial Rule, and the Báhêmbá in Sola, Northern Katanga, 1909-1960 - Loffman, Reuben (Journal of religion in Africa, 2015)
This article charts the history of a White Fathers’ mission in a challenging rural milieu on the margins of the Christian ‘kingdom’ they established in southeastern Congo. It follows the Society from their arrival in the town of Sola in 1909 to the end of the colonial period. The history of this mission contradicts Jan Vansina’s claim that missionaries in general were part of an ensemble of actors able to shatter a millennia-old political tradition in Central Africa. Their position on the margins of their Christian ‘kingdom’ meant that the White Fathers in Sola were not powerful enough to fully enforce their will on the population of the town. Rather, they struggled to gain converts before the First World War because they were unfamiliar with Sola. Afterward they had to compete with waged labour, Protestantism, and traditional ‘secret societies’ for Africans’ attention.